EVOLUTION OF THE LEDGER ACCOUNT. - Littleton, A. C. (The Accounting Review, 1926)
Abstract it is sometimes said that the basic principles of bookkeeping have not changed since the origin of double-entry in the middle ages. The statement is true if the term "basic principles" be closely construed but the casual reader is likely to interpret it broadly and thus carry away the impression that bookkeeping has to all intents and purposes stood still for 500 years. That idea would be erroneous, of course, because the forces of evolution act upon man's tools as well as upon man himself. Fundamental ideas regarding the nature of business transactions and theft recording have not changed in centuries but that is not equivalent to saying that progress has been absent or that evolution has not been at work. It is with the idea of noting the direction of some of these developments that a series of ledger accounts extending over nearly 500 years is studied here. A few of the available examples come from old ledgers, more of them are from the textbooks of the day. The illustrations given in such books are accepted as reasonably dependable examples of the then current practices, and in but few cases is there more than a fifty-year break in the date sequence of the texts examined.